PERJANJIAN TEMPAT PENITIPAN ANAK ORANG TUA YANG KURANG MAMPU DENGAN PERKUMPULAN SUNGAI KEHIDUPAN BORNEO TINJAUAN PASAL 1320 KUH PERDATA - Safarianingsih, Rini (Universitas Kapuas, 2025)
Handing over a child to a place of care in the form of an association is a hope for every parent who is unable to help with their child's education as long as the child is not yet able to carry out activities that generate income for themselves. With the existence of a religious-based day care that helps parents of children to educate and send them to school, it is hoped that this can help for the child's growth and development and future. Handing over child care is in accordance with the objectives, so both parties need to make an agreement regarding matters agreed in the interests of the child. The research method used is a descriptive analysis research method, the author conducted research on problems related to the validity of child care agreements made by parents with the Borneo Life River day care center in Melawi Regency.In discussion, the agreement between the child's parents and the Borneo River of Life service association is carried out on the basis of an agreement between both parties, if the child is accepted and fulfills several requirements requested by the association, the children under the auspices of the Borneo River of Life Association will provide the agreed regulations. Based on the description above, it can be concluded that the parent-child agreement with the Borneo Life River Association is an agreement with elements of good faith and trust where parents entrust their children to the Association so that the child can get a decent life and education from the Association and to realize their dreams. The Borneo River of Life Association in accepting students is selected by paying attention to the child's background and providing a decent education and life for the child. In order to realize the nation's ideals in general, namely realizing intelligence in the life of the nation and state. Apart from that, the Borneo River of Life Association in nurturing students focuses on religious services.